Quinolones as a Potential Drug in Genitourinary Cancer Treatment—A Literature Review - Kloskowski, Tomasz; Frąckowiak, Sylwia; Adamowicz, Jan; Szeliski, Kamil; Rasmus, Marta; Drewa, Tomasz; Pokrywczyńska, Marta (Frontiers in Oncology, 2022)
Quinolones, broad-spectrum antibiotics, are frequently prescribed by urologists for many urological disorders. The mechanism of their bactericidal activity is based on the inhibition of topoisomerase II or IV complex with DNA, which consequently leads to cell death. It has been observed that these antibiotics also act against the analogous enzymes present in eukaryotic cells. Due to their higher accumulation in urine and prostate tissue than in serum, these drugs seem to be ideal candidates for application in genitourinary cancer treatment. In this study, an extensive literature review has been performed to collect information about concentrations achievable in urine and prostate tissue together with information about anticancer properties of 15 quinolones. Special attention was paid to the application of cytotoxic properties of quinolones for bladder and prostate cancer cell lines. Data available in the literature showed promising properties of quinolones, especially in the case of urinary bladder cancer treatment. In the case of prostate cancer, due to low concentrations of quinolones achievable in prostate tissue, combination therapy with other chemotherapeutics or another method of drug administration is necessary.